Multi-vector model of urban planning - Арслан Баракбаев; Сеймур Мамедов; Аршын Ожет; Меруерт Байдрахманова; Леонид Булыга; Елена Феоктистова; Юлия Мазина (Проект Байкал)
In 1997, the government decided to move the capital of the Republic of Kazakhstan from Almaty to Astana. Analyses of urban sites and a sociological survey of the population revealed the shortcomings of the capital. The existing model of urban planning, which is conceptual in nature, allows construction clients to adjust detailed neighbourhood planning projects and narrows down architectural activity and responsibility to the boundaries of the planned site. The proposed multi-vector model of urban planning is more optimized, open to the public and comprehensive.